Students’ Engagement dalam Proses Pembelajaran Daring Melalui Lesson Study pada Mata Kuliah Kalkulus Integral - Iin Ariyanti; Fikrie Fikrie; Dyta Setiawati Hariyono (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
Students' engagement in the learning process is very important to identificate because it affects student success in the learning process. Students’ engagement is a psychological process that shows the attention, interest, investment, effort, and involvement of students which is poured into learning work includes emotional, cognitive, and behavioral engagement. This study aimed to see students' engagement in the online learning process through lesson study because from the beginning, the learning process had good planning (plan, do & see). This study used a qualitative-quantitative approach where the qualitative approach in this study aimed to produce an in-depth description of student engagement based on speech, writing and behavior observed by the observer during the stage of "do" lesson study while the quantitative approach aimed to determine students’ engagement from the point of students' views through a survey. Based on the results of the study, it was found that there were differences in the qualitative and quantitative results of student engagement in integral calculus students. In the qualitative analysis, only 12 out of 22 people showed student engagement during class discussions and/or group discussions. The rest are classified as not showing visible participation, only being seen taking notes, writing, or counting as well as facial expressions that show trying to understand the material presented, but there is still no involvement even though they are in a smaller group. Meanwhile, based on the results of quantitative analysis, there are no students who feel that their student's engagement is low both from the emotional, cognitive, and behavioral aspects.